2013
DOI: 10.1177/0004563213494078
|View full text |Cite
|
Sign up to set email alerts
|

Peri-operative troponin monitoring using a prototype high-sensitivity cardiac troponin I (hs-cTnI) assay: comparisons with hs-cTnT and contemporary cTnI assays

Abstract: Background: Non-cardiac surgery is associated with major vascular complications and higher incidences of elevated plasma troponin (cTn) concentration. Goal-directed therapy (GDT) is a stroke volume (SV)-guided approach to intravenous (IV) fluid therapy that improves tissue perfusion, oxygenation and reduces post-operative complications. In patients undergoing major gastro-intestinal surgery, we compared high sensitive and contemporary troponin assays and correlated results with patient outcome. Methods: Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…35 Several troponin assays are commercially available, and differences in performance in the perioperative setting have been described. 12 The clinical and biochemical findings of our study concur with findings of two smaller single-centre trials investigating postoperative troponin concentration after haemodynamic therapy 11 12 and of a recently published systematic review, which examined the association between haemodynamic therapy and cardiac complications. 4 Studies have found that peak postoperative troponin is correlated with outcome.…”
Section: Discussionsupporting
confidence: 87%
“…35 Several troponin assays are commercially available, and differences in performance in the perioperative setting have been described. 12 The clinical and biochemical findings of our study concur with findings of two smaller single-centre trials investigating postoperative troponin concentration after haemodynamic therapy 11 12 and of a recently published systematic review, which examined the association between haemodynamic therapy and cardiac complications. 4 Studies have found that peak postoperative troponin is correlated with outcome.…”
Section: Discussionsupporting
confidence: 87%
“…Perioperative troponin increases occurred most frequently for hsTnT, but the only troponin assay significantly related to mortality was hs-cTnI [28]. Perioperative troponin increases occurred most frequently for hsTnT, but the only troponin assay significantly related to mortality was hs-cTnI [28].…”
Section: Noncardiac Surgerymentioning
confidence: 96%
“…On the other hand, an isolated postoperative hs-cTn above the 99th percentile has to be interpreted carefully considering the global clinical picture, including preoperative levels. There are also sex-related differences to consider: men have higher hs-cTn values compared with women [28,31,32]. There are also sex-related differences to consider: men have higher hs-cTn values compared with women [28,31,32].…”
Section: Noncardiac Surgerymentioning
confidence: 99%
“…The minimum concentration of the fth-generation hs-ctnt STAT assay is 3 pg/ml, and its positive predictive value is approximately 95%. cTnI is a unique contractility protein, its normal values range from 0 to 0.03 g/L, cTnI ≥0.04 g/L can be diagnosed as myocardial infarction [6] , and the positive predictive value of the third-generation enhanced AccuTnI assay is approximately 60 . Although hs-cTnT and cTnI are both sensitive indicators for the detection of myocardial injury, hs-cTnT and cTnI have the risk of missing early myocardial injury.…”
Section: Introductionmentioning
confidence: 99%